Endocervical adenocarcinoma associated with lobular endocervical glandular hyperplasia showing rapid reaccumulation of hydrometra. Issue 6 (1st October 2008) - Takeuchi, K.; Tsujino, T.; Sugimoto, M.; Yoshida, S.; Kitazawa, S.
Abstract : Mucinous endocervical adenocarcinoma is characterized by increased watery vaginal discharge, but the early diagnosis is sometimes difficult because biopsy specimen might only serve to sample a superficial part of the tumor. The patient presented with complaints of abdominal distention. No vaginal bleeding or watery discharge was observed. Hydrometra was suspected by imaging studies. Rapid reaccumulation of hydrometra was seen despite drainage. Papanicolaou smear of endocervix and endometrium followed by fractional curettage was performed, but failed to confirm the diagnosis. To investigate the unknown origin of hydrometra, an exploratory laparotomy with total hysterectomy and bilateral salpingo-oophorectomy was performed, followed by pelvic lymphadenectomy because biopsy specimens during operation suggested adenocarcinoma of the cervix. The final pathologic study of surgical specimens revealed mucinous adenocarcinoma, which was located on the proximal area of cervix. Adjacent to carcinoma tissue, lobular endocervical glandular hyperplasia (LEGH) was detected. Pyloric gland mucin (HIK1083), MUC6, and MUC5AC were diffusely immunopositive in the cytoplasm of LEGH cells and the immunoreactivity became weaker in adenocarcinoma cells with tumor progression and loss of differentiation. Based on histopathologic features of the present case, there seems to be a possible link between LEGH and conventional mucinous endocervical adenocarcinomas. The physician should keep in mind the possible existence of endocervical adenocarcinoma in a patient showing rapid reaccumulation of hydrometra, when uterine malignancies are clinically suspected and biopsy finding fails to confirm the diagnosis.